PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) BERBASIS LIVEWORKSHEET PADA TEMA 8 DAERAH TEMPAT TINGGALKU SUBTEMA 2 KEUNIKAN DAERAH TEMPAT TINGGALKU - Putri Clara Rimayanti; Nita Karmila; Fitri Anjaswuri (STKIP Subang, 2023)
The Electronic Student Worksheet (E-LKPD) is a work guide for students to make it easier for students to engage in learning activities in electronic form that can be accessed via computers or mobile phones. This research is a Research and Development (RnD) study, with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which aims to produce an innovative electronic student worksheet (E-LKPD) based on Liveworksheet in class IV theme 8 sub-theme 2 learning 1 that deserves to be developed. The research was conducted at Julang Elementary School, Bogor City, with a total of 22 students in the 2022-2023 school year. The research began by analyzing the needs of students' worksheets, observing students working on LKPD, then making product designs. Then develop the product and validate the product with experts in their field which are then tested on a limited basis with respondents. The results of the validation trial stated that the product was very feasible with an average value of 94.5%. The results of the limited trial stated that the Liveworksheet-based E-LKPD was in the very feasible category with an average value of 87.6%. Based on the results of the study, it can be interpreted that the Liveworksheet electronic-based student worksheets are very feasible to use